Use of digital signage in academic libraries in Nigeria (2013)
The application of information and communication technologies (ICTs) in libraries has been expanding all over the world. All the functions and services that academic librarians used to provide manually are now being provided through the use of ICTs which can do things better and faster. Most modern day libraries are interested in the various infrastructure networks that serve as major channels for the transmission of information. ICTs include a variety of rapidly evolving technologies such as telephony, cable, satellite, television and radio, video conferencing, computers, information networks, and software applications. However, most of the libraries have not explored the use of digital signage for the dissemination of information to their patrons. As computer technology continues to evolve and the demand for hard copy materials reduces, the desire to visit academic library is on the decline. In order to make library more relevant in this era of ICT, digital signage, which is one of the telecommunication technologies can be used as a channel to provide information that will attract lecturers, students, researchers, and the academic community to the library. This paper highlighted the benefits that can be derived from the use of digital signage in improving the provision of library and information resources and services and also the challenges . It also advocated that digital signage should be introduced to the academic libraries , because of the benefits that can be derived from its usage.